Tophaceous Gout and Renal Insufficiency: A New Solution for an Old Therapeutic Dilemma. (14th May 2011) - Tausche, Anne-Kathrin; Wunderlich, Carsten; Aringer, Martin
Abstract : The prevalence of gout is increasing with increased life expectancy. Approximately half of the patients with gout have some degree of renal impairment. If both conditions persistently coexist, and in severe tophaceous gout, in particular, treatment has been difficult. We here report on the case of an 87-year-old woman, who had been suffering from recurrent gouty arthritis over 4 years. Monthly polyarthritis attacks were accompanied by subcutaneous tophi. Serum uric acid levels were constantly above 600  μ mol/L (10 mg/dL). Allopurinol was no option because of intolerance, while benzbromarone was ineffective because of renal impairment. Therefore, the novel xanthin oxidase inhibitor febuxostat was started, achieving rapid control of serum urate levels (<360  μ mol/L). After initial worsening of inflammation in the first weeks, gouty attacks stopped and all tophi resolved within the following 10 months. Renal function remained stable.